MATHEMATICAL MODELING OF ELASTIC WAVE VELOCITY ANISOTROPY IN A CRACKED GEOLOGICAL MEDIUM - Maslov B.P.; Prodaivoda G.T.; Vyzhva S.A. (My University, 2001)
A new method has been proposed for the mathematical modeling of the effective elastic constants of a geological medium with arbitrary one, two or three oriented systems of cracks. The method imposes no restrictions as to the concentration or shape of the cracks. Numerical calculations using a "cracked limestone" model have established essential differences between transverse-isotropic and azimuthal-anisotropic velocity of elastic waves with various types of polarisation travelling in "cracked limestone" with different systems of cracks. The established factors can be applied in determining crack systems with seismic methods.